Europe and Central Asia Economic Update, Fall 2020 : COVID-19 and Human Capital - World Bank (Washington, DC: World Bank, 2020)
The COVID-19 pandemic has hit human capital directly in Europe and Central Asia, adversely affecting both education and health. School closures may lead to learning losses equivalent to a third to a full year of schooling, and they are likely to exacerbate inequalities, by disproportionately affecting students from disadvantaged backgrounds. The disease has already killed thousands of people, and some patients who survive will suffer long-term damage to their health. Recovery from the pandemic will thus require strong investment in education and health. This update examines human capital outcomes in the region and the ways in which the pandemic is likely to affect them. A focus on the quality of tertiary education and health risk factors of obesity, smoking, and heavy drinking highlights the challenges that are particularly important for the region. Post-COVID 19 policy initiatives to improve education and health will need to recognize the challenges posed by increased reliance on remote learning and the importance of being prepared for future pandemics, given the vulnerability of the region’s aging societies and the large number of people with underlying health risks.